2021
DOI: 10.1007/s00259-021-05574-y
|View full text |Cite
|
Sign up to set email alerts
|

Proof of concept of a multimodal intravital molecular imaging system for tumour transpathology investigation

Abstract: Background Transpathology highlights the interpretation of the underlying physiology behind molecular imaging. However, it remains challenging due to the discrepancies between in vivo and in vitro measurements and difficulties of precise co-registration between trans-scaled images. This study aims to develop a multimodal intravital molecular imaging (MIMI) system as a tool for in vivo tumour transpathology investigation. Methods The proposed MIMI system in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Several PET inserts in 7T or 9.4T MRI have been reported, such as Hyperion II and MADPET4 with digital silicon photomultiplier technology ( 41 47 ). Recently, Liu et al reported a multimodal intravital imaging system that provided a coregistered in vivo trans- scale and transparent platform (PET, MRI, microscopy) and quantitative evaluation of tumor anatomy, vasculature, and the microenvironment, including glucose, oxygen, and acidity metabolism ( 48 ).…”
Section: Hybrid Imagingmentioning
confidence: 99%
“…Several PET inserts in 7T or 9.4T MRI have been reported, such as Hyperion II and MADPET4 with digital silicon photomultiplier technology ( 41 47 ). Recently, Liu et al reported a multimodal intravital imaging system that provided a coregistered in vivo trans- scale and transparent platform (PET, MRI, microscopy) and quantitative evaluation of tumor anatomy, vasculature, and the microenvironment, including glucose, oxygen, and acidity metabolism ( 48 ).…”
Section: Hybrid Imagingmentioning
confidence: 99%
“…The dorsal skinfold window chamber (DSWC) is a model that can be used to directly study the occurrence, progression, and response of drugs to the treatment of living animals, especially for tumor angiogenesis, tumor microenvironment changes, and research on treatment. 27 In 1943, Moy et al first proposed the DSWC, which was fixed by the use of two aluminum chassis in the back of rats through continuous improvement. 28 Presently, the model can be applied to live animals, such as mice, and the fixed frame is also changed from aluminum to titanium or lighter materials.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, DSWC can also be applied to fluorescence and photoacoustic imaging, ultrasound, magnetic resonance imaging (MRI), positron emission tomography (PET) imaging, and multimodal imaging. 27,29,30 Many studies on DSWC have shown the structural and functional differences between tumor blood vessels and normal blood vessels and can quantitatively study tumor blood vessels and normal blood vessel permeability, hemoglobin saturation, and other parameters. In addition, DSWC models enable us to further understand the microcirculation and metabolism of tumors and study living animals at the cellular and molecular levels.…”
Section: Introductionmentioning
confidence: 99%